THE GENERALITY AND IDIOSYNCRASY OF VERB FORMATION IN MADURESE LANGUAGE - Mohammad Halili (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The current research aims to scrutinize the generality and idiosyncrasy of verb formation mirrorred in Madurese language. The language has been easily understood and intuitively acknowledged for native speakers. Since the (ir)regularity, changing a word in shapes and functions, also demonstrates its linguistic facet, the approach from morphological explanation becomes crucial. This is to provide background information for those especially interesting in learning the language and or simply making even the native speakers aware of. Furthermore, it would be beneficial in a way that the proper uses both syntactically and semantically are appropriate. This employed the explanatory research, collecting the data from WA (WhatsApp) group. All members are indigenous of Madura and thus the group facilitates the extensive use of the given language. By identifying, capturing and classifying the required data, they were subsequently analyzed from the proposing morphological underpinnings. The findings of this research demonstrate that prefix a- and –e are considered to be bound morphemes as they cannot stand alone. They function to form a verb in active voice and a verb in passive voice. The generality takes place. The idiosyncrasy is, however, also phenomenal.